IDENTIFYING MARINE PROTECTED AREAS TO SUPPORT FISHERIES SUSTAINABILITY ON BALI ISLAND USING THE LARVAL PARTICLE TRACKING METHOD - Aldi Vyacta Pranayena S., Gede
The utilization of Marine Protected Areas (MPAs) in Indonesia as a tool to support sustainable fisheries requires a solid scientific foundation for its design. In this study, the design, determination, and clustering of MPAs were conducted based on particle tracking simulations. Particle tracking or trajectory modelling was carried out by releasing particles along the coast of MPAs around Bali Island, only for the period from November to February. The Python Ocean Parcels repository equipped with the capability to compute Lagrangian particle trajectories using high-order time integration through the Runge-Kutta fourthorder scheme, was employed. The connectivity matrix of each MPA, along with its network centrality, was computed using the NetworkX module in the Python programming language. Based on the conducted simulations, the connectivity matrix results revealed that Bali Island and Lombok Island are the primary larval importers in their surrounding areas during the months of November to February. The distribution of larvae originating from Bali and Lombok Islands to all MPAs is greatly influenced by the current movements in the Lombok Strait and Alas Strait during the mentioned period. Furthermore, four MPAs were identified as having the ideal distance for a networked Marine Protected Area system, exhibiting mutual import and export connectivity. These MPAs are Meru Betiri National Park, Nusa Penida MPA, West Lombok MPAs, and Central Lombok MPAs.